THE DESIGN OF DETERGENT WASTE PROCESSING USING INTERNET OF THINGS - Ma'arief, Shandy Auliya; Sabila, Liya Yusrina; Amelia, Shinta (Transient: Jurnal Ilmiah Teknik Elektro, 2024)
Detergent is a product that is widely used by people to clean clothes. Detergent production contains synthetic dyes which can contain heavy metals such as Cadmium (Cd) and Cuprum (Cu). The remainder of detergent use is usually thrown into the environment, in this case we call it detergent waste. Detergent waste must be managed and processed in an environmentally friendly manner and meet environmental quality standards before being discharged into the environment. The heterogeneous Fenton method will be chosen to solve this problem. Another challenge that needs to be resolved is time inefficiency in processing detergent waste, where users have to carry out processing manually so they spend time just waiting for the waste processing process. In this research, a tool was created to overcome the problem of batik waste processing using an Internet of Things-based waste processing reactor using color sensors. This research concludes that a detergent waste processing reactor using an IoT-based color sensor can carry out the detergent waste degradation process. The reading of the color sensor value is carried out based on the frequency value on a scale of 20%. Determining the RGB value mapping on the color sensor is the result of 20% scaling of the frequency read by the sensor with mapping values R = 35 Hz, G = 53 Hz, and B = 40 Hz as the lower limit and R = 159 Hz, G = 174 Hz, and B = 211 Hz as the upper limit of the frequency read.